Post a New Question

PreCal

posted by .

Solve for x.

-3x^2+8=-4

  • PreCal -

    -3x^2 = -12
    x^2 = 4
    x = ±2

  • PreCal -

    thanks and what about this one ?
    Simplify the expression

    (3x^-1y^2)^3(5x^2y)0

    I'm getting confused because of the negative exponent

  • PreCal -

    anything^0 = 1, so we just have

    (3x^-1y^2)^3 = 27 x^-3 y^6 = 27y^6/x^3

    negative exponents indicate a swap between numerator and denominator

    x^-3 = 1/x^3

    1/x^-3 = x^3

    recall that x^a/x^b = x^(a-b)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question